Educational Policy : The Art Of Decision Making For Economics Student Internship Program - Karuniana Dianta Arfiando Sebayang; Darma Rika Swaramarinda (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aims to evaluate the Internship Program which is required by Faculty of Economics and find out the extent of success of the Internship Program in order to develop human skills, and formulate policy recommendations to improve such activities in the future. This research uses descriptive deductive method and model evaluation of the Context-Input-Process-Product ( CIPP ) program. From the research result, it is found that implementation in context, input, process and product aspects has been done with various results. There are 6 issues of strategic issues raised based on interviews that are considered to be considered in regard to the internship program. Researchers also give 6 policy recommendations to be implemented by the faculty that will impact on the human development of the world of education in general.